Acute Haematogenous Metacarpal Osteomyelitis in Children: A Case Report and Review of Literature - Jordi Colomina Morales; Laura Soria Villegas; Joan Carles Monllau García (Case Reports in Infectious Diseases)
Metatarsal osteomyelitis in children is a very uncommon disease, and this can make diagnosis difficult leading to a delay in treatment that can cause complications like brachymetacarpia or loss of function. We present an infant affected by granulomatous chronic disease with acute haematogenous osteomyelitis of the fourth metacarpal. Serratia marcescens was found to be the pathogenic agent. Treatment was antibiotics and debridement. Bone healed with little length discrepancy but functional result was normal.